A solar-driven photocatalytic fuel cell with dual photoelectrode for simultaneous wastewater treatment and hydrogen production1. Issue 7 (21st February 2015) - Wu, Zhongyi; Zhao, Guohua; Zhang, Yajun; Liu, Jian; Zhang, Ya-nan; Shi, Huijie
<x xml:space="preserve">Abstract</x> A solar-driven dual photoelectrode photocatalytic fuel cell (PFC) based on n-type semiconductor photoanode and p-type semiconductor photocathode is reported for wastewater treatment with simultaneous hydrogen production.